2012
DOI: 10.1111/j.1540-6237.2012.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

It's Complicated: Latinos, President Obama, and the 2012 Election*

Abstract: Objective Assess Latino support past, present, and future for President Obama and his policies, and the role of the Latino vote in the 2012 election. Methods Examine Latino voting patterns, administrative decisions and legislation enacted by President Obama affecting Latinos, and Latino public opinion polls to evaluate potential support for Obama by Latinos. Results Despite disappointment and anger over immigration policy by President Obama, Latinos still indicate high levels of support for him and willingness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…We use this measure as a proxy to gauge feelings of anxiety and concern about immigration enforcement that may be detrimental to individuals in their lives. Research has shown that immigration is a highly personal and salient issue to Latinos in part because of how it affects their families, neighbors, friends, and communities (Wallace 2012;Sanchez et al 2015). We expect that individuals who express high levels of concern about potential immigration enforcement will also be more likely to support immigrant rights activism.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…We use this measure as a proxy to gauge feelings of anxiety and concern about immigration enforcement that may be detrimental to individuals in their lives. Research has shown that immigration is a highly personal and salient issue to Latinos in part because of how it affects their families, neighbors, friends, and communities (Wallace 2012;Sanchez et al 2015). We expect that individuals who express high levels of concern about potential immigration enforcement will also be more likely to support immigrant rights activism.…”
Section: Methodsmentioning
confidence: 98%
“…Research has shown that immigration is a highly personal and salient issue to Latinos in part because of how it affects their families, neighbors, friends, and communities (Wallace 2012;Sanchez et al 2015). In fact, these types of personal social networks played a key role in motivating and mobilizing many Latinos to participate in the historic 2006 protest wave (Bloemraad and Trost 2008;Zepeda-Millan 2016).…”
Section: Immigration Racialization and Social Networkmentioning
confidence: 99%
“…Studies that explore Latino presidential approval are limited, but extant research does suggest that there are a few key policy issues of special import to the Latino community broadly (Sanchez et al 2012; Stokes-Brown 2006; Wallace 2012; Branton 2007; Sanchez 2006). As Latinos have become a growing sector of the electorate, scholars have become increasingly interested in the circumstances in which Latinos vote as a group and what their unique policy interests might be.…”
Section: Presidential Approvalmentioning
confidence: 99%
“…As Latinos have become a growing sector of the electorate, scholars have become increasingly interested in the circumstances in which Latinos vote as a group and what their unique policy interests might be. This scholarship has identified immigration and healthcare as issues of special import to the Latino community (Sanchez et al 2012; Wallace 2012). Research in this vein was explicitly connected to presidential approval, as scholars endeavored to anticipate Latino support for the President’s 2012 bid for reelection, and worked from the perspective that President Obama had made certain promises on immigration reform during the 2008 election that he failed to follow through on in his first term.…”
Section: Presidential Approvalmentioning
confidence: 99%
See 1 more Smart Citation